The nurse practitioner-led primary health care clinic : a community needs analysis : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Nursing at Massey University - Clendon, Jill (Massey University, 1999)
Aim. To determine the feasibility of establishing a nurse practitioner-led, family focused, primary health care clinic within a primary school environment as an alternate or complementary way of addressing the health needs of 'at risk' children and families to the services already provided by public health nurses. Method. Utilising needs analysis method, data was collected from three sources - known demographic data, 17 key informant interviews and two focus group interviews. Questions were asked regarding the health needs of the community, the perceptions of participants regarding the role of the public health nurse in order to determine if a public health nurse would be the most appropriate person to lead a primary health care clinic, and the practicalities of establishing a clinic including the services participants would expect a clinic to provide. Analysis was descriptive and exploratory. Results. A wide range of health needs were identified from both the demographic data and from participant interviews. Findings also showed that participants' understanding of the role of the public health nurse was not great and that community expectations were such that for a public health nurse to lead a primary health care clinic further skills would be required. Outcomes from investigating the practicalities of establishing a nurse practitioner-led clinic resulted in the preparation of a community-developed model that would serve to address the health needs of children and families in the area the study was undertaken. Conclusion. Overall findings indicated that the establishment of a nurse practitionerled, family focused, primary health care clinic in a primary school environment is feasible. While a public health nurse may fulfil the role of the nurse practitioner, it was established that preparation to an advanced level of practice would be required. It is likely that a similar model would also be successful in other communities in New Zealand, however the health needs identified in this study are specific to the community studied. Further community needs assessments would need to be completed to ensure health services target health needs specific to the communities involved.
Keywords: Community health services; Primary care (Medicine); Nurse practitioners; New Zealand; Research Subject Categories::INTERDISCIPLINARY RESEARCH AREAS::Health and medical services in society